Analisis Visi Misi Guru Pak Dalam Konteks Kurikulum Merdeka Ditinjau Dari Perspektif Filsafat Pendidikan Kristen - Elfin Warnius Waruwu; Mortan Sibarani (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
This study aims to analyze the philosophy of Christian education related to the vision and mission of Christian religious education teachers in the context of an independent curriculum. The main focus of this study is to introduce the basic concepts and principles of Christian education philosophy that are relevant to understanding the vision and mission of Christian religious education teachers. This study also identifies the contribution of Christian educational philosophy to the development of an independent Christian curriculum. This study uses a descriptive analysis method to study the relevant concepts and principles of Christian education philosophy. Various theoretical sources, such as Christian educational philosophy literature and the Bible, are used to support the analysis. This research reveals that the vision and mission of Christian religious education teachers emphasize the recognition of God's divinity, love as the main principle, the integration of faith and knowledge, the formation of Christian character, and the spiritual dimension of education. In implementing their vision and mission, Christian religious education teachers can use content selection that supports Christian values, integrated teaching strategies, and relevant assessments. In this way, they can create learning experiences that reflect their vision and mission and help students develop strong Christian character.